Studies in alcoholic liver disease in Britain: 1 Clinical and pathological patterns related to natural history. Issue 1 (January 1974) - Brunt, P. W.; Kew, M. C.; Scheuer, P. J.; Sherlock, Sheila
Abstract : A group of 258 patients with various forms of alcoholic liver disease—steatosis, mild and severe hepatitis, and cirrhosis—has been studied. Severity of disease as judged histologically did not correlate very well with clinical presentation although signs of hepatocellular failure were certainly commoner in severe hepatitis and cirrhosis. Fever, pigmentation, and clubbing were also pointers to these two conditions. Alcoholic hepatitis is probably precirrhotic and carries a poor prognosis and the best laboratory indicators of this are moderate elevation of white cell count and bilirubin. Prognosis in alcoholic liver disease is significantly improved by abstinence from alcohol.